Bank competition and account penetration: Evidence from Mexico - Ana Georgina Marín; Rainer Schwabe (Banco de México, 2013)
This paper documents a positive relation between bank competition and the penetration of bank accounts at the municipal level in Mexico. To account for potential biases in our regressions due to the endogeneity of market structure, we employ a two-stage estimation approach based on an equilibrium structural model. Our preferred estimate implies that moving from a monopoly to a duopoly will lead to an increase of 1,016 accounts per 10,000 adults, a 42% increase over the cross-municipality mean. This is comparable to the effect of large increases in per capita income and years of schooling, or the establishment of an additional branch by a bank who is already present in the local market. Our results suggest that competition policy should be given a prominent role in the financial inclusion agenda.
Keywords: O16; G21; L13; D43; 330; financial inclusion; banking; competition